Profile of Students' Science Literacy Ability in Solving Physics Problems (Universitas Negeri Surabaya, 2023)
Abstract The research was conducted for the profile identifying the literacy capabilities of the scientists in solving global warming materials. This is descriptive research and the method of data collection is carried out with written tests and elevation of students. The results obtained were then analyzed using quantitative descriptive methods. This study is done on 68 students of Class X in State High School 1 Kepohbaru, which showed that students of class X have very high literacy skills, although some students are still in very low categories. Scientifically phenomenal indicators have a presentation of 52%, indicators designing and evaluating scientifically research have a presentation of 40%, and indicators interpret scientific evidence and data have a Presentation of 31%. Based on the data, it can be concluded that the profile of students' ability to be scientifically literate in solving problems questions of physics is still very low. The level of science literacy ability also influences the problem solving, the better the problem resolution, the higher the profile of scientific literacy skills of students. Keywords: Profile, Scientific literacy skills, problem solving